Towards formulating a specific legislation on the law of presumption of death in Malaysia - Mohd Noor, Nor Azlina; Abd. Aziz, Ahmad Shamsul; Halim, Akmal Hidayah (Indian Journal of Public Health Research and Development, 2018)
The existing law in Malaysia authorized an evidence of existence of physical body before the law recognized the end of presumption of life of person. Hence, problem may arise where a person has been missing and his whereabouts is not known to the person close to them as no declaration of dead can be made as there is no body to support the contention. This article seeks to examine the specific law in England & Wales namely Presumption of Death Act 2013 in order to suggest an appropriate legal framework on presumption of death in Malaysia. For this purpose, the discussion adopts the doctrinal analysis by examining the existing primary and secondary materials includes statutory provisions, case law and other legal and non-legal literatures relating to the presumption of death and missing persons. This article concludes that there is a need to propose a specific legislative act to harmonize the uncertainties in the existing legal framework. There must be a statutory recognition of ‘specific peril’ rules to circumvent the hardship of seven years common law waiting period. The law must have following features which are, the court must have jurisdiction's over the property of the missing person; notice to the presumed missing person must be attempted; the lapse of time before the presumption can be raised must be reasonable and there should be some safeguard for the missing person should he return.